PENGARUH PENDIDIKAN GIZI DAN PESAN GIZI MELALUI SHORT MESSAGE SERVICE (SMS) TERHADAP PENINGKATAN KADAR HEMOGLOBIN IBU HAMIL DI KABUPATEN BANTUL - Nila Susanti Hamam Hadi Anis Fuad (Berita Kedokteran Masyarakat (BKM), 2012)
Background: Some studies report that low compliance with iron tablet taking in pregnant mothers is mainly caused by factor of forgetfulness. When forgetfulness becomes the main cause of incompliance with iron tablet taking, the presence or participation of husband or media to remind pregnant mothers is very important. One type of interpersonal communication that can be an alternative in efforts to improve nutrition awareness of the community especially pregnant mothers to increase compliance with iron tablet taking is the delivery of SMS as reminder combined with nutrition education of mothers. Objective: To find out impact of nutrition education and nutrition message through SMS to increase of hemoglobin level pregnant mothers at District of Bantul. Method: The study used a quasi experimental design (non equivalent control group design). The intervention given to subject of the study consisted of nutrition education using nutrition education method and SMS as reminder of nutrition and health of pregnant mothers and motivation for compliance with iron tablet taking. Group 1 got nutrition education and SMS, group 2 got nutrition education and group 3 was control group. Result: The result of Anova statistical test showed there was no difference (p=0.96) in increase of hemoglobin level in the experiment groups. The result of multivariate analysis showed that initial hemoglobin level of pregnant mothers and compliance of pregnant mothers with iron tablet consumption affected increase of hemoglobin. Conclusion: Nutrition education with SMS did not affect increase in hemoglobin level of pregnant mothers. Nutrition education did not affect increase in hemoglobin level of pregnant mothers. Initial hemoglobin level and compliance with Fe tablet taking affected increase in hemoglobin level of pregnant mothers. Keywords: nutrition education, SMS, hemoglobin, pregnant mothers